2021
DOI: 10.3390/ijms23010208
|View full text |Cite
|
Sign up to set email alerts
|

TARBP2 Suppresses Ubiquitin-Proteasomal Degradation of HIF-1α in Breast Cancer

Abstract: TAR (HIV-1) RNA binding protein 2 (TARBP2) is an RNA-binding protein participating in cytoplasmic microRNA processing. Emerging evidence has shown the oncogenic role of TARBP2 in promoting cancer progression, making it an unfavorable prognosis marker for breast cancer. Hypoxia is a hallmark of the tumor microenvironment which induces hypoxia-inducible factor-1α (HIF-1α) for transcriptional regulation. HIF-1α is prone to be rapidly destabilized by the ubiquitination–proteasomal degradation system. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Under the circumstance of hypoxia, HIF-1α is negatively regulated by FBXW7-mediated ubiquitination and proteolysis in human ovarian cancer cells, proposing an underlying direction for energy reprogramming and angiogenesis ( 91 ). The oncoprotein TAR (HIV-1) RNA binding protein 2 (TARBP2) can elevate the stability of HIF-1α by decreasing its ubiquitination level through decreasing the E3 ligases activity including FBXW7 in BC cells ( 125 ).…”
Section: Fbxw7 and The Hallmarks Of Cancermentioning
confidence: 99%
“…Under the circumstance of hypoxia, HIF-1α is negatively regulated by FBXW7-mediated ubiquitination and proteolysis in human ovarian cancer cells, proposing an underlying direction for energy reprogramming and angiogenesis ( 91 ). The oncoprotein TAR (HIV-1) RNA binding protein 2 (TARBP2) can elevate the stability of HIF-1α by decreasing its ubiquitination level through decreasing the E3 ligases activity including FBXW7 in BC cells ( 125 ).…”
Section: Fbxw7 and The Hallmarks Of Cancermentioning
confidence: 99%
“…HIF-1α is regulated by pro-inflammatory cytokines (IL-1b, and TNF-α,) in an NF-kB-dependent manner. The level of protein is controlled for example by TARBP2, which prevents its proteasomal ubiquitination to enhance HIF-1α protein stability [ 117 ]. A significant correlation of these proteins is observed with breast cancer pathogenesis, and progression process, and is linked to hypoxia.…”
Section: Micrornas (Mirnas) In Breast Cancermentioning
confidence: 99%
“…In breast cancer, Parkin and TNF receptor-associated factor 6 have been shown to target the ubiquitination of HIF-1α. In addition, GSK-3β can mediate the degradation of HIF-1α in hepatoma cells through FBXW7 ( 20 - 22 ). These studies suggested that FBPs may have a role in HIF-1α regulation.…”
Section: Introductionmentioning
confidence: 99%